The Pragmatic Presuppositions of somebody/someone in Christian Religious Discourse in Nigeria - Dada, Samuel Ayodele; Mercy, Omoregbe Esohe (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The study examines the pragmatic presuppositions of somebody and someone as being employed by preachers in Christian ministration discourse in Nigeria. The study aims at investigating the pragmatic motivations behind the use of these pronouns in Churches by preachers. The study identifies the necessity of the context of situation as the major reason behind the use of these pronouns. Indeed, somebody is here is the language of God to His people in such an occasion. The study has once more brought to the fore the merit of the campaign that a writer/speaker needs good training not only in the grammatical competence but also in the communicative competence of the language with which he operates.